ANALISIS KELAYAKAN FINANSIAL USAHA BUDIDAYA KARAMBA JARING APUNG DI KOPERASI BONTANG ETA MARITIM KOTA BONTANG - Dwi Novitasari Subagio; Bambang Indratno Gunawan; Oon Darmansyah (2339-1324, 2021)
This research aimed to analyze the financial feasibility of floating net cages in Bontang Eta Maritim Cooperation and to know the profit sharing pattern in Bontang Eta Maritim Cooperation. This research was conducted in January 2019 in floating cage of Bontang Eta Maritim Cooperation. The sampling method used was using census or total sampling with the total respondent of 30 people. The research result indicated that the recent cultivation business of floating net cages was financially feasible with NPV value by IDR3.218.655, IRR by 21%, Net B/C by 1.73 and Payback Period by 2.90 years (2 years 8 months 24 days). The analysis result of cultivation sensitivity in floating net cages on the operational cost and maintenance (O and M) increased by 4% and the total revenue or income decreased by 3,5% indicating that this cultivation business is not feasible to be developed (no go). The profit-sharing pattern between PT. Pupuk Kalimantan Timur and Bontang Eta Maritim Cooperation was 50%: 50% from the yields. For the cultivator, the Cooperation cut IDR5,000/kg from the total yield. Furthermore, the keeper of the floating net cages was given fee as much as IDR50,000/day.